Dziesięć zabaw z czasem. Konceptualizacja czasu w poezji Inny Lesnianskiej - Nikadem-Malinowska, Ewa (Studia Rossica Posnaniensia, 2012)
Inna Lisnianska, a Russian poet born in 1928, debuted in the late 1950s and has been publishing intellectual and inspired poetry since then. One of her major artistic achievements has been the creation of the linguistic concept of time. The poems that were selected for this analysis show the poet’s ability to recognize the signs of time “in everything” (M. Bachtin).